Welfare Comparison of Leader-Follower Models in a Mixed Duopoly - Aiyuan Tao; Yingjun Zhu; Xiangqing Zou (Journal of Applied Mathematics)
In the standard leader-follower duopoly models with otherwise symmetric firms, the market outcome and total welfare are the same whichever firm is the leader. This paper studies and compares total welfare in a sequential-move mixed duopoly when either the public firm or the private firm acts as the leader. It is found that the fact that which firm is the leader affects total welfare and that whether firms compete in quantity or price also affects the optimal choice of market leader.